The potential cost of regulation of methane and nitrous oxide emissions in U.S. agriculture - Tshepelayi Kabata; Lilyan E. Fulginiti; Richard K. Perrin (CABI Agriculture and Bioscience)
Abstract Background Most studies on the environmental impacts of agriculture have attempted to measure environmental impacts but have not assessed the ability of the sector to reduce or mitigate such impacts. Only a few studies have examined greenhouse gas emissions from the sector. This paper assesses the ability of states in the U.S. to reduce agricultural emissions of methane and nitrous oxide, two major greenhouse gases (GHGs) with important global warming potential. Methods The analysis evaluates Färe’s PAC (pollution abatement cost) for each state and year, a measure of the potential opportunity costs of subjecting the sector to GHG emissions regulation. We use both hyperbolic and directional distance functions to specify agricultural technology with good and bad outputs. Results and conclusions We find that such regulations might reduce output by an average of about 2%, although the results for individual states vary quite widely.